Group Exhibition-Noi, French Cultural Center Naples, Palazzo di Cultura di Vaticano Morcone Museum, Morcone, Italy - Antoniou, Klitsa (My University, 2026)
Noi, French Cultural Center Naples, Palazzo di Cultura di Vaticano Morcone Museum, Morcone, Italy Curated by Antonio Manfredi and Marco Menegutso